The Effect of Balikpapan-Samarinda Toll Road Construction with a PPP Scheme on The Formation of Economic Structure in East Kalimantan - Aisyah Tarassyta; Ilmiawan Auwalin (JIET (Jurnal Ilmu Ekonomi Terapan))
Economic effects are just one of the many effects of the massive infrastructure investment in Indonesia made over the past ten years. The aim of connecting Indonesia between regions is the basis for massive infrastructure growth, especially toll road infrastructure. Several funding schemes have been implemented to build toll road infrastructure, including the Public-Private Partnership (PPP) financing scheme. This PPP financing scheme was also implemented in the Balikpapan-Samarinda toll road construction. Therefore, this research attempts to capture the impact of the construction of the Balikpapan-Samarinda toll road with a PPP scheme on the formation of the economic structure in East Kalimantan province using the Input-Output (I-O) table. The investment value for the Balikpapan-Samarinda toll road is IDR 9.97 trillion was injected (shock) into gross fixed capital formation in the construction sector. The calculation results in this research show that the construction of the Balikpapan-Samarinda toll road contributed 9.8% of total demand. Apart from that, there is a significant impact on the economic structure of East Kalimantan Province, as seen from the expenditure multiplier figure with an output total of IDR 15,111 billion, a total income of IDR 2,471 billion, and a total workforce of 25,095 workers due to investment in the construction of the Balikpapan-Samarinda toll road.